2018
DOI: 10.1016/j.biombioe.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Regional socio-economic impacts of intensive forest management, a CGE approach

Abstract: The demand for and supply of forest biomass have both been increasing in recent years, which will set new requirements for forest management. Thus, new studies on regionally suitable forest management regimes to fulfill the needs of potential new investments and the impacts on wood supply potential on regional socioeconomic welfare are called for. The aim of this study was to examine the impacts of intensive forest management due to increased demand for wood biomass, from the regional economy point of view. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Table 3 shows that GOP, vegetables, and perennial plantations grown on mineral soils have higher (Table 3). Improvements in supply of primary productivity Firstly, not cultivated and overgrown agricultural land on mineral soils with soil quality points less than 25 on mineral soils are transferred to managed coniferous forests on mineral soils, because biomass production in intensively managed forests is on average 26% higher than in unmanaged forests (Karttunen et al, 2018) and higher potential for biomass production is shown by coniferous stands (Nord-Larsen and Pretzsch, 2017). Secondly, not cultivated and overgrown agricultural land on organic soils is transferred to managed coniferous forests on organic soils, because afforestation of well-drained organic soils increases biomass production (Weslien et al, 2009), also this measure increases carbon sequestration in the soil, which is another soil function which we expect from our soils although we are not investigating that in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows that GOP, vegetables, and perennial plantations grown on mineral soils have higher (Table 3). Improvements in supply of primary productivity Firstly, not cultivated and overgrown agricultural land on mineral soils with soil quality points less than 25 on mineral soils are transferred to managed coniferous forests on mineral soils, because biomass production in intensively managed forests is on average 26% higher than in unmanaged forests (Karttunen et al, 2018) and higher potential for biomass production is shown by coniferous stands (Nord-Larsen and Pretzsch, 2017). Secondly, not cultivated and overgrown agricultural land on organic soils is transferred to managed coniferous forests on organic soils, because afforestation of well-drained organic soils increases biomass production (Weslien et al, 2009), also this measure increases carbon sequestration in the soil, which is another soil function which we expect from our soils although we are not investigating that in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The trickle down effects and indirect implications of the challenge should also be examined. For instance, anti-carnivore sentiment will likely only grow as climate change and pressures to confine pastoral herders makes livestock more difficult to raise (P. G. Jones and Thornton 2009;Lindsey, Romañach, and Davies-Mostert 2009). Many large carnivores are already threatened and endangered, and further anthropogenic pressures on the populations will lead to severe declines in populations including potential extinction of keystone species (Towns et al 2009;Bagchi and Mishra 2006;Johnson et al 2006); but it is often associated with underlying human-human conflict (A. J. Dickman 2010).…”
Section: Propose Implications Of Ignoring This Challengementioning
confidence: 99%
“…At the minimum, exploration of a hope-for-the-best strategy or minimal intervention is critical because of costs. Business-as-usual models can also provide an economic mechanism to value ecosystems services (Fu et al 2018;Karttunen et al 2018), and whilst this is not without debate, this can expand the breadth of stakeholders and potential investors in a solution for a particular challenge. A best and worst case scenario analysis is also likely a frequent need for many environmental challenges because of inertia in the socio-political structures that we use to manage people and resources.…”
Section: Propose Implications Of Ignoring This Challengementioning
confidence: 99%
“…The total production volume of the plant was assumed to be 200,000 tons per year and the total capital investment of the plant was assumed to be 45.5 million euros based on the study by Svanberg et al [13]. Karttunen et al [14] studied the total regional socio-economic benefits of sawmill and bio-coal investments, which were supported by the intensive forest management at the South Savo region. As a Journal of Sustainable Bioenergy Systems result, the regional benefits could be annually 2.8% (150 M€) for GDP more than in BAU scenario by 2030 including multiplier effects [14].…”
Section: Introductionmentioning
confidence: 99%
“…Karttunen et al [14] studied the total regional socio-economic benefits of sawmill and bio-coal investments, which were supported by the intensive forest management at the South Savo region. As a Journal of Sustainable Bioenergy Systems result, the regional benefits could be annually 2.8% (150 M€) for GDP more than in BAU scenario by 2030 including multiplier effects [14].…”
Section: Introductionmentioning
confidence: 99%